Budaya Masyarakat setelah Masuknya BRIlink di Desa Labaraga Kecamatan Wakorumba Utara Kabupaten Buton Utara - Wa Ode Asfiani; Ashmarita Ashmarita (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This study aims to find out and describe the culture of the community after the culture of the community after the entry of BRILink in Labaraga Village, North Wakorumba District, North Buton Regency. This study uses the theory of Cultural Interpretation of Clifford Geertz in Erlan Tedio Fawas by using a qualitative descriptive method. The data collection technique used is using observation and in-dept interviews. The results of this study indicate that the culture of the community after the inclusion of BRILink in Labaraga Village. With the development of science and technology, BRILink user in Labaraga Village have experienced changes. This change started with following the trend, thus motivating people to become BRILink agents as a service for the BRILink user community, where initially transactions at BRILink were still very minimal. However, as time goes by, transactions at BRILink are increasingly being used by the people of Labaraga Village and now it has become a habit for the community because transactions and other systems have become more practical.